Pembuatan Sabun Padat Dari VCO (Virgin Coconut Oil) Dan Ekstrak Buah Mentimun (Cucumis sativus L.) - ., rahmayulis; Putri, Rahmi; Ranova, Riki (LPPM Akademi Farmasi Imam Bonjol Bukittinggi, 2023)
Cucumber fruit extract is known to contain several secondary metabolites such as flavonoids, saponins, and alkaloids which have antioxidant effect that are useful in making soap.This study aims to determine the effect of cucumber fruit extract on solid soap quality standards. Cucumber fruit is extraxted by maceration method and making VCO (Virgin Coconut Oil) with traditional method. Condensed extract of cucumber fruits is formulated into soap preparations with a concentration of 1g, 2g and 3g. The physical evaluation parameters of the preparation studied were organoleptic tests. pH tests, Moisture content tests and free alkali content tests which were carried out every week at room temperature storage for a period of 4 weeks. The results showed that the VCO (Virgin Coconut Oil) soap formula with cucumber fruit extract produced solid soap that was stable in organoleptic testing, and met the pH standard of solid soap